Aspects concerning the acoustical performance of school buildings in Portugal - Pinho, P.G. (2016)
Acoustic measurements were performed in eight schools of different levels of education (from kindergarten to college) located in Viseu – Portugal. The acoustic evaluation was made in order to analyze the most common problems that may condition the acoustic environment inside school building. The acoustics evaluation of school buildings was made by the measurement of: reverberation time in classrooms; sound insulation between classrooms and between classrooms and corridors; impact sound insulation of floors and airborne sound insulation of façade. The sound insulation of façade was made with all elements closed and with natural ventilation conditions (banners or windows tilt mode). It was found that most of the studied cases revealed disabled constructive aspects in relation to the acoustic requirements of school buildings compromising the quality of education.